Private Junior High School Marketing Management to Face the New Students Admission (PPDB) Policies of State Junior High School in Surabaya - Damayanti, Sinta Putri; Khamidi, Amrozi; Karwanto, Karwanto (International Journal for Educational and Vocational Studies, 2021)
This study was conducted to determine the marketing strategy of private schools in facing the new policies of the Surabaya City Office in the Admission of New Junior High School Students. Various internal and external factors also influence the running of the marketing strategy being implemented. This study focuses on: a) marketing strategy including school programs, strategy and gold mix (product, price, location, promotion of human resources, sarpras and service management), b) internal factors including school strengths, school weaknesses and organizational structure, c) factors external includes school opportunities, school threats and political technology, culture. The method used is qualitative research and case study type. The subjects in this study are the principal, the Deputy Principals, especially in the field of public relations who know the relationship between the institution and the wider community, teachers as learning actors, guardians of students as consumers of service users. This research was conducted in the odd semester of the 2019-2020 school year. Data collection techniques using observation, interviews, and documentation. The data analysis technique used in this study was an interactive analysis model consisting of three components, namely data condensation, data triangulation, data presentation and conclusion drawing.The results showed that the marketing strategies implemented by the Labschool Junior High School and Kemala Bhayangkari 1 Surabaya Junior High School were good and maximized by taking advantage of the advantages they had. Inhibiting factors, such as new policies and the number of competitors, can be minimized by continuing to prioritize superior programs and explore existing human resources.